Exploring student perspectives on intellectual capital role within university environments / Salwa Muda ... [et al.]. - Muda, Salwa; Che Mohamed, Che Norhalila; Musman, Musliha; Mohamed Sadique, Raziah Bi; Hussin, Amariah Hanum (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Intellectual capital, encompassing human capital, structural capital, and relational capital, holds a vital role in shaping the educational landscape of universities. As universities seek to provide holistic educational experiences, understanding how students perceive the different dimensions of intellectual capital becomes paramount. By understanding how students view intellectual capital, the university can align its resources and efforts to enhance the learning experience. Despite the growing recognition of intellectual capital's significance for improving an organization’s value creation, there is a lack of research on intellectual capital in the university context, particularly regarding students' perceptions. Therefore, this study aims to bridge this gap by investigating students' perceptions of human capital, structural capital, and relational capital, thereby providing insights into the role of intellectual capital in contributing to the university's overall reputation. An online questionnaire survey was carried out to 130 students from UiTM Cawangan Negeri Sembilan, Kampus Seremban. The data were analyzed using IBM SPSS Statistics 25 software. Mean score analyses were conducted to evaluate students' perceptions of intellectual capital. The results show that students have overwhelmingly positive views regarding intellectual capital on average. Their perceptions suggest that they not only recognize but also appreciate the importance of human capital, structural capital, and relational capital within the university environment. It signifies a harmonious alignment between the university's offerings and students' expectations. This alignment can lead to many positive outcomes, benefiting students, faculty, alumni, and other stakeholders.